Grounded Theory: A Practical Overview of the Glaserian School - Biaggi, Carlos; Wa-Mbaleka, Safary (JPAIR Multidisciplinary Research, 2018)
In many parts of the world, qualitative research is still new. This can be evidenced in the limited number of qualitative research theses, dissertations, and journal article publications in Asian higher education institutions and journals. In fact, many institutions hardly offer qualitative research courses in their graduate programs. However, qualitative research is steadily growing. More and more people in many different fields are embracing it. Looking at the historical foundation of qualitative research, it is important to recognize the first publication of a qualitative research design by Glaser and Strauss (1967) half a century ago. This book is generally accepted as the pioneering work in the field of qualitative research. This manuscript presents an overview of what the classical grounded theory by these two pillars of qualitative research is all about and examples of how to implement it effectively in carrying out a research study. This manuscript is intended to provide a practical understanding of grounded theory for novice qualitative researchers and a refresher for experienced ones.